HOMOLOGI FUNGSI GEN KNAT1 ( Knotted 1– like Arabidopsis thaliana) PADA ANGGREK BULAN Phalaenopsis amabilis (L.) Bl. DENGAN MEDIATOR Agrobacterium tumefaciens - Sulastri Isminingsih; Endang Semiarti; Aziz Purwantoro (Jurnal Agroekoteknologi, 2009)
ABSTRACTTo understand the function of KNAT1 gene Arabidopsis in the forming and developing of Indonesian origin orchid shoot Phalaenopsis amabilis through transform p35S::KNAT1 and pGreen to protocorm like bodies (plb) of the orchid mediated by Agrobacterium tumafaciens LBA4404. The plb transformants were grown on New Phalaenopsis selection medium containing 5 mg/l BAP, 0.15 mg/l NAA, 15 mg.l Kanamycin and addition of 300 mg/l Cefotaxim to eliminate the overgrowth of Agrobacterium. The analysis of positive transformant use Polimerase Chain Reaction (PCR) with the specific oligonucleotide primers for KNAT1 gene: KNAT1F1R1 and universal primers for pGreen: 35SO and Tnos. The result shows that 3 shoots of 1850 transformants positively carry out the 35S::KNAT1 construct (frequency of transformation was 0.16 %) while 5 shoot of 1850 transformants also positively carry out the pGreen vector, with the frequency of transformation was 0.27 %. The phenotype analysis of 35S::KNAT1 transformants show multiplication on forming of the leaf from a plb to + 10 shoots and forming of the leaf shape which has terompet like shapes and rectangular shape.Key words: Arabidopsis, KNAT1 gene, Phalaenopsis amabilis, shoot